Values of wisdom in Indonesian and German proverbs - Merry Lapasau (Universitas Indraprasta PGRI, 2017)
Since ancient times traditional societies continued their practical knowledge and life experiences through language from generation to generation so that each community group has a source of behavioral rules that can be used as a guide for life. Linguists, historians, anthropologists, social observers, cultural experts or literary specialists or anyone who wants to understand the concept of community life can have it from the expression of language in the form of advice, slogans, proverbs, phrases, anecdotes, parables and proverbs. This study discusses the time concepts contained in the Indonesian and German proverbs by focusing on the functions and values of wisdom contained therein. This research uses descriptive qualitative approach and is expected to explain about the philosophy, teaching and reflection of the height of thought of the ancient Indonesian people and the values contained in the German proverb.